Morphological and molecular characteristics of Milandanielia intermedia (Feider, 1950) (Trombidiformes: Microtrombidiidae) with data on its biology and ecology - Felska, Magdalena; Mąkol, Joanna (Zootaxa, 2015)
Milandanielia intermedia (Feider, 1950) is re-described. A female from which larvae were obtained by experimental rearing is designated as neotype. Verified diagnoses of active life instars are supplemented with data on habitat preferences, phenology and life cycle. Molecular identification of the species based on its COI sequence is provided.